Gerakan Islam Politik Milli Gorus dan Perempuan (Martabat: Jurnal Perempuan dan Anak, 2023)
This article discusses the views of Milli Gorus, anIslamic political movement from Turkey, on women, familyand gender, and the position of women in the movement. TheMilli Gorus Movement is the umbrella, or parent organization,of a number of Islamic parties in Turkey. A number of Islamicparties were born out of the Milli Gorus Movement. One ofthese Islamic parties is the AKP. Since 2002 this party has wonthe elections. After years of controlling the Turkish statebureaucracy, the AKP has succeeded in reorganizing theIslamic aspects of the Republic of Turkey in the face ofmodernity, secularism, and neoliberalism. Another aspect thatneeds to be studied is issue on women. After so many years ofpolitical Islam controlling Turkey, a question arise whether theirperspective on women, family and gender changed. What is theMilli Gorus movement's view on the matters? To answer it, Ipresent an overview of the emergence of the women'smovement in Turkey, then discusses the views of the MilliGorus movement regarding this matter. I assume that the viewsof the Milli Gorus movement remain conservative andunchanged, although in some cases they are flexible.